Analysis on Platform Merdeka Mengajar (PMM): Does It Affect Teachers’ Workload and Well-being? - Kamarullah, Kamarullah; Istiarsyah, Istiarsyah; Maisura, Maisura; Maulya, Ranti; Bahri, Samsul (Universitas Pahlawan Tuanku Tambusai, 2024)
The widespread integration of digital teaching platforms in education has prompted an exploration of their impact on teacher workload and well-being. This research focuses on understanding the effects of Platform Merdeka Mengajar (PMM), a prominent digital teaching platform in Indonesia, on the workload and well-being of participating high school teachers in Banda Aceh Municipality and Great Aceh Regency, Aceh Province, Indonesia. Utilizing a qualitative descriptive research design, six teachers were interviewed to explore their experiences with PMM. Thematic analysis of the interviews revealed that while PMM offers valuable resources and fosters professional collaboration, it also increases workload and stress due to additional preparation time and the need for technological adaptation. The study highlights the importance of providing targeted training, improving the platform's usability, and enhancing its integration features to mitigate these challenges. Despite its limitations, including a small sample size and potential biases in qualitative data, the study provides insights into the potential benefits and challenges of integrating digital platforms into educational practices in Indonesia. The findings underscore the need for a balanced approach to technological integration that supports teachers' professional development and well-being. A more supportive access is necessary to develop the digital platform to balance the nuanced dynamics of teachers’ workload and well-being.